Transfer pricing as a tax compliance risk - Sven P. Jost; Michael Pfaffermayr; Hannes Winner (University of Salzburg, Department of Social Sciences and Economics, 2010)
This paper contributes to the empirical literature on the transfer pricing behavior of multinational firms. Previous research mainly focuses on transfer pricing as a means of tax optimization. Our approach concentrates on transfer pricing as a critical compliance issue. Specifically, we investigate whether and to what extent the awareness of transfer pricing as a tax compliance issue responds to country and industry characteristics as well as firm-specifics. Empirically, the transfer pricing risk awareness is measured as a professional assessment reported by the person with ultimate responsibility for transfer pricing in their company. Based on a unique global survey conducted by a Big 4 accounting firm in 2007 and 2008, we estimate the number of firms reporting transfer pricing being the largest risk issue with regard to subsequent tax payments. We find that transfer pricing risk awareness depends on variables accounting for general tax and transfer pricing specific strategies, the types and characteristics of intercompany transactions the multinational firms are involved in, their individual transfer pricing compliance efforts and resources dedicated to transfer pricing matters.
Keywords: F23; H25; 330; Transfer pricing; International taxation; Multinational firms; Tax risk management